Analisis Kehidupan Sosial Ekonomi Masyarakat Etnis Jawa di Nagari Lubuk Gadang Selatan Kecamatan Sangir Kabupaten Solok Selatan : Penelitian - Siska Widyawati; Nurdawani Putri Insyani; Nurfazlin Nova (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the socio-economic conditions of the Javanese ethnic community in Nagari Lubuk Gadang Selatan, Sangir District, Solok Selatan Regency, using a descriptive qualitative approach. Data were collected through interviews, observation, documentation, and literature review, and validated with source and theory triangulation. The analysis covered population, households, ethnicity, religion, social interaction, local wisdom, age, education, occupations, commodities, and asset ownership. The findings show variations in socio-economic conditions: harmonious social interaction, preserved local wisdom, low education levels, and the majority working as tea plantation laborers or farmers cultivating commodities such as cinnamon, coffee, rice, corn, and chili. In general, household income is sufficient to meet daily needs.